Unconventional digital computing approach: memristive nanodevice platform. Issue 1 (20th November 2014) - Shahsavari, Mahyar; Faisal Nadeem, M.; Arash Ostadzadeh, S.; Devienne, Philippe; Boulet, Pierre
Abstract Memristor is a two‐terminal nanodevice that has recently attracted the attention of many researchers. Its simple structure, non‐volatility behavior, high‐density integration, and low‐power consumption make the memristor a promising candidate to act as a switch in digital gates for future high‐performance and low‐power nanocomputing applications. In this paper, we model the behavior of memristor by using Verilog‐A. To investigate its characteristics in a circuit, we use the HSPICE simulator. Furthermore, a library of digital gates are provided by using two approaches to make digital gates: the first one is based on material implication (IMP) and the second one is based on crossbar arrays. Finally, we perform a comparison and evaluation between the two methods. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)